PENERAPAN PERSIDANGAN SECARA ELEKTRONIK DI PENGADILAN NEGERI SUMATERA BARAT - Ulfanora, Ulfanora; Amelia, Dian; Aziz, Harry Azhar (Jurnal Hukum Bisnis Bonum Commune, 2022)
The Supreme Court stipulates Supreme Court Regulation Number 1 of 2019 in the context of reforming case administration and court proceedings to overcome service barriers in court, especially in the implementation of simple, fast and low-cost principles as well as demands for the development of the era of technology and information as well as the challenges of the Covid-19 pandemic. The application of this Supreme Court regulation also known as e-Court which is a service used for administration in the lawsuit process, simple lawsuits, rebuttal requests, payment of court fees, conducting court summons and notifications, trials, decisions, and legal remedies electronically. The results of the study explain that all District Courts in West Sumatra have implemented e-Court, minimized the occurrence of things that harm the parties, made the case process simpler, accelerated the period of the case and suppressed the expenditure of court fees in accordance with the simple, fast and low-cost principle. However, in practice, there are main problems, namely the lack of Human Resources in the use of technology and information.